The role of residence advisors in student academic advice and success: insights and experiences from a university of technology - Isheachida Manatsa; Mzwandile Khumalo (Journal of Student Affairs in Africa)
Student achievement is a central objective for higher education institutions. To advance this goal, continuous enhancements in academic support services and interventions have been introduced within Higher Education Institutions (HEIs). Initiatives like academic advice, increasingly emphasize an interconnected approach, acknowledging the significant impact of out-of-class learning environments on student accomplishments. The out-of-class learning environment encompasses various components that include study spaces, recreational facilities, and student housing accommodation. However, limited research on the connectedness between student housing, academic advising and student success exists.  Informed by the basic tenets of the validation theory, this study sought to explore the impact of student housing on academic advice and student success with a specific focus on the contributions of Residence Advisors (RAs). Thirteen [N=13], Residence Advisors [RAs] from Durban University of Technology responded to an online open-ended questionnaire administered through Google Forms. Data indicated that RAs functioned as a primary point of contact for students experiencing problems affecting their academic work. A vital role offering academic guidance and counselling significantly influencing the academic progress of students residing at respective facilities was performed by the advisors. However, the RAs had received minimal or no formal training on the provision academic advice. The study recommends that RAs get training on academic advising for improved efficacy of their critical role on student attainment.